Retrospective research: identifying and conducting phylogenetic analyses on four Orf virus strains isolated in Yunnan province between 2021 and 2023—revealing their significance and characteristic features - Xie, Jiarui; Kou, Meiling; Wang, Yinan; Su, Xiaohang; Gao, Huafeng; Miao, Haisheng (Frontiers in Veterinary Science, 2024)
Contagious Eczema (CE), caused by ORFV, impacts sheep and goats globally, with severe symptoms and economic losses. The ORFV situation in Yunnan, China, was unclear before 2021–2023 study. Eleven scab samples from goats on small farms in three Yunnan municipalities were collected. Four ORFV strains were isolated and characterized using scanning electron microscopy, cytopathic effect observation, and PCR. Phylogenetic analyses of ORFV011 and ORFV059 genes showed significant results. For ORFV011, the nucleotide similarity of the four strains to D1701 strain was 98.4–99%. For ORFV059, it was 97.2–97.9% with OV-SA00 strain. These findings suggest gene rearrangements and interactions among strains during Yunnan’s ORFV outbreak, forming a unique evolutionary lineage. Our study is the first comprehensive one on Yunnan’s ORFV prevalence with in-depth phylogenetic analysis. It has important implications. In vaccine development, understanding genetic variances helps create better vaccines. For disease control, customized strategies like targeted quarantine and disinfection can be designed based on strain characteristics. From a public health aspect, as CE is zoonotic, closely monitoring ORFV in goats aids in predicting and preventing human infections, thus being significant for protecting goats against CE in Yunnan.